Pathological Anatomy of Olive Tumors Caused by Pseudomonas savastanoi - FUDL-ALLAH, ABD EL-SHAFY A.; BARAKA, MOHAMED M. (The Libyan Journal of Agriculture, 2023)
Samples from healthy and infected olive, Olea europaea L., twigs with Pseudomonas savastanoi were sectioned and studied before and after fixation. The following anatomical characteristics of tumor formation in olive were observed: (i) hypertrophy and hyperplasia; (ii) dissolution and disruption of cells resulting in fissures around the bacteria; (iii) differentiation of tumor cells into disarranged and malformed tracheary elements; and (iv) bacteria overwinter in pockets within the xylem and under favorable conditions will move through fissures toward outside the tumor.